Psychosocial Interventions in the Treatment of Child and Adolescent Conduct Disorder - Ayşegül Tonyalı; Zeynep Göker; Özden Şükran Üneri (Psikiyatride Güncel Yaklaşımlar, 2019)
Since conduct disorder is a mental disturbance deteriorating not only children or adolescents’ functioning but both their close environment and even the whole society they live in, it is crucially important to be treated with effective interventions. There is mainly child, family and school-oriented interventions for childhood-onset conduct disorder and treatments of adolescent-onset conduct disorder include community and institutional practices in addition to adolescent, family and school-oriented interventions. Approaches to childhood-onset conduct disorder based on social learning theory, and interventions of adolescent-onset conduct disorder built on “needs, responsivity and risk principles” seem to be effective treatment modalities. Family-oriented approaches using concurrently either adolescent school-oriented interventions or society-oriented programs appear to be the most effective treatments for short-term and long-term outcomes. Adolescents with high risk and advanced age seem to have better progress with interventions whereas sexual offenders are less likely to benefit from treatment than the other conduct pathologies.